Early access disparities in innovative therapies across the US, EU, China, and Japan - Akodad, Sanae; Goldman, Michel; Stevens, Hilde (Frontiers in Medicine, 2025)
Early access to innovative therapies offers a critical lifeline for patients with severe or life-threatening conditions, yet substantial disparities persist across the United States (US), the European Union (EU), China (CH), and Japan (JP). These disparities arise from diverging definitions of unmet medical need (UMN), heterogeneous timelines for regulatory review, and uneven implementation of Early and Expanded Access mechanisms. This policy review provides a comparative analysis of regional frameworks, emphasizing how clinical trial geography, eligibility rules, and access mechanisms interact to shape pre-approval opportunities for patients. While regulatory innovations such as the FDA's Breakthrough Therapy designation, the EMA's PRIME scheme, the PMDA's Sakigake program, and recent reforms in China have accelerated access in selected contexts, cross-border misalignments and fragmented health technology assessment (HTA) processes continue to generate inequities. The EU's new HTA Regulation (2021/2282) represents a step forward by embedding joint clinical assessment and real-world evidence, but persistent structural inconsistencies hinder timely and equitable uptake. This article argues for a paradigm shift from static approval models to adaptive licensing approaches, including live licenses and regulatory sandboxes. It calls for internationally coordinated benefit–risk governance that integrates early access planning into drug development from Phase II onward. By reframing uncertainty as a shared responsibility among regulators, developers, payers, clinicians, and patients, early access governance can be redesigned to promote equity, transparency, and responsiveness particularly for rare and high-burden diseases.